A GntR-Like Transcription Factor HypR Regulates Expression of Genes Associated With L-Hydroxyproline Utilization in Streptomyces coelicolor A3(2) - Kotowska, Magdalena; Świat, Michał; Zarȩba-Pasławska, Justyna; Jaworski, Paweł; Pawlik, Krzysztof (Frontiers in Microbiology, 2019)
Bacteria from the genus Streptomyces have been long exploited as the most prolific producers of antibiotics, other secondary metabolites and enzymes. They are important members of soil microbial communities that can adapt to changing conditions thank to the fine regulation of gene expression in response to environmental signals. Streptomyces coelicolor A3(2) is a model organism for molecular studies with the most deeply recognized interactions within the complex metabolic and regulatory network. However, details about molecular signals recognized by specialized regulatory proteins as well as their direct targets are often missing. We describe here a zinc-binding protein HypR (SCO6294) which belongs to FadR subfamily of GntR-like regulators. The DNA sequence 5’- TACAATGTCAC-3’ recognized by the HypR protein in its own promoter region was identified by DNase I footprinting. Binding of six DNA fragments containing similar sequences located in other promoter regions were confirmed by the electrophoretic mobility shift assay. The sequences of 7 in vitro-determined binding sites were assembled to generate a logo of the HypR binding motif, 5’-CTNTGC(A/C)ATGTCAC-3’. Comparison of luciferase reporter genes expression under the control of cloned promoter regions in S. coelicolor A3(2) wild type and deletion mutant strains revealed, that the HypR protein acts as a repressor of its target genes. Genes belonging to the regulon of HypR code for enzymes putatively involved in collagen degradation and utilization of L-hydroxyproline (L-Hyp) as concluded from predicted structure and conserved domains. Their transcription is induced in the wild type strain by the addition of L-Hyp to the culture medium. Moreover, knockout of one of the genes from the predicted L-Hyp utilization operon abolished the ability of the strain to grow on L-Hyp as a sole source of carbon. To our knowledge, this work is the first indication of the existence of the pathway of L-hydroxyproline catabolism in Streptomycetes.